Charging the internal combustion engine - Hiereth, Hermann; Prenninger, Peter (Wien Springer, 2007)
This book covers all aspects of supercharging internal combustion engines. It details charging systems and components, the theoretical basic relations between engines and charging systems, as well as layout and evaluation criteria for best interaction. Coverage also describes recent experiences in design and development of supercharging systems, improved graphical presentations, and most advanced calculation and simulation tools.
Text in English, translated from German.